Social treatment among the Aymara - Llanque Chana, Domingo (1973)
Every human group develops norms and criteria for the social behavior of its members in their interpersonal and community relationships. These norms of human conduct make up the art of living in good relations with one's fellow men. The Aymaras of the Qollao plateau behave according to the rules of conduct developed through centuries of their culture's existence. In my attempt to get to know and expose the criteria for the interpersonal and community relationships of the Aymaras, I have collected on tape the interview I conducted in the Aymara language about what an Aymara peasant lives and thinks about his social behavior.